Using Exponential smoothing Models in Forecasting about The Consumption of Gasoline in Iraq (Journal of the College of Basic Education, 2022)
In this paper, the exponential smoothing approach is used in order to forecast about the consumption of Gasoline in Iraq for the years from 2014 to 2024 making use of the data obtained from the Oil Products Distribution Company. In this situation, three methods were applied, namely, Single, Double, and Winters' exponential smoothing. We employ; the mean absolute percentage error (MAPE), the mean absolute deviation (MAD) and mean squared deviation (MSD) as a criterion for compare between these methods. And we conclude that the winters' method is the best according to MAPE and MAD criterion. Key Words: Forecasting , exponential smoothing , Single exponential smoothing , Double exponential smoothing , Winters' exponential smoothing , MAPE(mean absolute percentage error), MAD(mean absolute deviation), MSD(mean squared deviation).